1989
DOI: 10.1159/000185674
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Renal Hemodynamic but Conserved Natriuretic Response to Dopamine in Patients with Renal Disease

Abstract: Renal hemodynamics and sodium excretion were determined before and during infusion of dopamine in doses ranging from 0.25 to 8 μg/kg/min in healthy volunteers (n = 15) and in patients with renal disease and moderately impaired renal function (n = 21, baseline glomerular filtration rate 34–85 ml/min). While in normal volunteers dopamine resulted in marked renal vasodilation (maximal fall in filtration fraction 24%), in patients with moderately impaired renal function, the renal vasodilatory response to dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…This increased loss is not sustained with chronic use of glucocorticoids and has not been seen by all investigators. Dopamine in doses of 0.25-8 mg.kg À1 .min À1 has been shown to have a phosphaturic effect both in healthy volunteers and in patients with renal failure [36].…”
Section: Loss Of Phosphate From the Bodymentioning
confidence: 99%
“…This increased loss is not sustained with chronic use of glucocorticoids and has not been seen by all investigators. Dopamine in doses of 0.25-8 mg.kg À1 .min À1 has been shown to have a phosphaturic effect both in healthy volunteers and in patients with renal failure [36].…”
Section: Loss Of Phosphate From the Bodymentioning
confidence: 99%
“…In a recent study, doseresponse analysis of dopamine in water-loaded individuals was performed. 103 It was found that the natriuretic and renal vasodilating effect of dopamine was maximal at a dose of 3 g ⅐ kg Ϫ1 ⅐ min…”
mentioning
confidence: 99%
“…Corroborating our results, other authors have also shown that renal function is not improved with LDD for patients undergoing cardiac surgery 16 or liver transplantation, 17 or for those in postoperative states, 15,16,31 critically ill with oliguria, 13 or with previous renal diseases. 14 Other recent studies have confirmed these findings. In a double-blind, randomized, multicenter, placebo-controlled study with a large number of severely ill patients (n = 328), 18 treatment with LDD did not seem to be advantageous.…”
Section: Discussionmentioning
confidence: 52%
“…The effect of LDD on natriuresis may be explained by its inhibition of aldosterone, 14 and by its direct action on the proximal renal tubules. 10 In some studies in which a significant increase in sodium excretion was detected, the patients were suffering from congestive cardiac failure, 4,12 but other studies have found higher excretion even in patients without cardiac disease.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation